2016
DOI: 10.1158/0008-5472.can-15-1567
|View full text |Cite
|
Sign up to set email alerts
|

Improved Treatment of Breast Cancer with Anti-HER2 Therapy Requires Interleukin-21 Signaling in CD8+ T Cells

Abstract: The HER2/ErbB2 monoclonal antibody (mAb) trastuzumab is combined with chemotherapy as a standard-of-care for newly diagnosed HER2þ breast cancer patients, but some patients treated with this combination therapy experience early relapse. Our analysis of data from a clinical trial evaluating the efficacy of chemotherapy plus/minus trastuzumab suggested that the magnitude of trastuzumab benefit on distant disease-free survival was higher for increasing expression of the IL21 receptor (IL21R). Therefore, we invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Beyond the activation of CD8 + T cells, IL-21 can suppress Tregs (42)(43)(44). In contrast, IL-2, a cytokine widely evaluated in preclinical and clinical studies, promotes both CD8 + T cells and Tregs (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the activation of CD8 + T cells, IL-21 can suppress Tregs (42)(43)(44). In contrast, IL-2, a cytokine widely evaluated in preclinical and clinical studies, promotes both CD8 + T cells and Tregs (45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of TILs in relation to the histological differentiation (G) revealed the ascension between low TILs presence and poorly differentiated histological grade (G3), also supported by the study by Hee Jin Lee et al, 2015. [7] The Ki-67 proliferation index is one of the major prognostic factors in breast cancer, independent of the status of the axillary lymph. [8][9][10][11][12][13][14] Its role as a predictive factor in establishing the neoadjuvant and adjuvant treatment is controversial due to the conflicting results obtained in various studies.…”
Section: Resultsmentioning
confidence: 99%
“…We and others showed that CD8 + T cells and IFN-γ were required for the anti-ErB2 mAb therapy. 1,3,4 In order to test whether CD8 + T cells and IFN-γ are also required for BsPD-L1xrErbB2 therapy, we depleted either CD8 + T cells or CD4 + and CD8 + T cells together, or neutralized mouse IFN-γ in the groups of mice treated with bispecific control Ig (B12), anti-PD-L1 and anti-ErbB2 combination therapy and BsPD-L1xrErbB2 therapy. As shown before, bispecific antibody therapy induced more tumor rejections compared to the anti-PD-L1 and anti-ErbB2 combination therapy group.…”
Section: Cd8 + T Cells and Ifn-γ Were Critical For The Anti-tumor Effmentioning
confidence: 99%
“…Rat ErbB2-positive H2N100 tumor cells were generated from female Balb/c MMTV-ErbB2/neu transgenic mice and cultured as described previously. 1,29 TUBO cells were cultured in complete DMEM supplemented with 10% heat-inactivated fetal calf serum (Thermo Scientific), 1X glutamax, 50 U/ml penicillin, 100 μg/ml streptomycin and 10 mM HEPES (Sigma-Aldrich), while other cell lines were cultured in RPMI supplemented with 10% heat-inactivated fetal calf serum, 1X glutamax, 50 U/ml penicillin, 100 μg/ml streptomycin, 1 mM sodium pyruvate from Gibco-Life Technologies and 10 mM HEPES, 1% non-essential amino acid solution, and incubated at 37°C in 5% CO 2 incubator. The anti-rat ErbB2 mAb (clone 7.16.4) hybridoma was kindly provided by Mark I. Greene (University of Pennsylvania, Philadelphia, PA).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation